Continuous Peripheral Nerve Block Compared With Single-Injection Peripheral Nerve Block: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 6 (1st November 2012) - Bingham, Ann E.; Fu, Rochelle; Horn, Jean-Louis; Abrahams, Matthew S.
Abstract : Background and Objectives: Many practitioners consider continuous peripheral nerve blocks (cPNBs) to be superior to single-injection peripheral nerve blocks (siPNBs). Several randomized controlled trials have demonstrated improved pain control, patient satisfaction, and other outcomes for patients with cPNBs compared with patients with siPNBs, whereas other trials have not shown significant differences. We sought to clarify any potential advantages of cPNBs over siPNBs. Methods: We conducted a systematic review and meta-analysis of all prospective, randomized trials comparing cPNBs with siPNBs. We used a validated systematic search strategy to identify potentially eligible studies. For studies meeting inclusion criteria, methodologic quality was scored independently by 2 reviewers. Data from the studies were abstracted and pooled for meta-analysis. Results: Compared with siPNBs, cPNBs were associated with a decreased rating of worst pain on postoperative day 0 (effect size [ES], −1.29; 95% confidence interval [CI], −2.19 to −0.40; P = 0.005), postoperative day 1 (ES, −1.87; 95% CI, −2.44 to −1.31; P < 0.001), and postoperative day 2 (ES, −2.03; 95% CI, −2.78 to −1.290; P < 0.001); decreased overall opioid use (ES, −15.70; 95% CI, −21.84 to −9.55; P < 0.001); less nausea (ES, 0.633; 95% CI, 0.407–0.983; P = 0.043); and higher patient satisfaction scores (weighted mean difference, −2.04; 95% CI, 1.24–2.85; P < 0.001). Conclusions: Compared with siPNBs, cPNBs were associated with improved pain control, decreased need for opioid analgesics, less nausea, and greater patient satisfaction. The effect of cPNBs on other clinically relevant outcomes, such as complications, long-term functional outcomes, or costs, remains unclear.